Rapid assessment of Opisthorchis viverrini IgG antibody in serum: A potential diagnostic biomarker to predict risk of cholangiocarcinoma in regions endemic for opisthorchiasis - Rutchanee Rodpai; Vor Luvira; Lakkhana Sadaow; Wattana Sukeepaisarnjaroen; Amnat Kitkhuandee; Krisada Paonariang; Oranuch Sanpool; Wannaporn Ittiprasert; Victoria H. Mann; Pewpan M. Intapan; Paul J. Brindley; Wanchai Maleewong (International Journal of Infectious Diseases, 2022)
Background: Opisthorchiasis is caused by an infection with fish-borne liver flukes of the genus Opisthorchis. Opisthorchiasis frequently leads to chronic inflammation in the biliary tract and is classified as a group 1 biological carcinogen by the International Agency for Research on Cancer: a definitive risk for cholangiocarcinoma (CCA). Methods: We used the rapid immunochromatographic test (ICT) to detect anti-Opisthorchis viverrini IgG and IgG4 subclass antibodies in sera of patients with CCA. The ICT kits were developed based on soluble antigens excreted and secreted by O. viverrini adult worms. Results: ICT indicated sera was positive for IgG and IgG4 antibodies, respectively, in 22 (61.1%) and 15 (41.6%) participants of the 36 study participants diagnosed with CCA (P > 0.05). Our study also included groups with other cancers and with liver cirrhosis, where the IgG ICT and IgG4 ICT kits were 27.7% (13/47) and 25.5% (12/47) positive, respectively (P > 0.05). Neither total the IgG ICT nor the IgG4 ICT yielded positive results in a control group of 20 healthy participants. Moreover, the percentage positivity rate using the ICT for total IgG between the CCA group and the other cancers and liver cirrhosis group was significantly different (P < 0.05). By contrast, no significant difference between these groups was apparent in the ICT for IgG4 antibody. The CCA group was 6.53 times more likely to have positive anti–O. viverrini IgG antibody (odds ratio 6.53, P < 0.001) and 3.27 times more likely to have positive anti–O. viverrini IgG4 antibody (odds ratio 3.27, P = 0.010) than the non-CCA group. Conclusion: This information is of potential value for the development of a diagnostic biomarker to predict risk for O. viverrini infection-associated CCA.